Utilizing GCaMP transgenic mice to monitor endogenous Gq/11-coupled receptors - Partridge, John G. (Frontiers in Pharmacology, 2015)
The family of GCaMPs are engineered proteins that contain Ca2+ binding motifs within a circularly permutated variant of Aequorea Victoria green fluorescent protein (cp-GFP). The rapidly advancing field of utilizing GCaMP reporter constructs represents a major step forward in our ability to monitor intracellular Ca2+ dynamics. With the use of these genetically encoded Ca2+ sensors, investigators have studied activation of endogenous Gq types of G-protein coupled receptors (GPCRs) and subsequent rises in intracellular calcium. Escalations in intracellular Ca2+ from GPCR activation can be faithfully monitored in space and time as an increase in fluorescent emission from these proteins. Further, transgenic mice are now commercially available that express GCaMPs in a Cre recombinase dependent fashion. These GCaMP reporter mice can be bred to distinct Cre recombinase driver mice to direct expression of this sensor in unique populations of cells. Concerning the central nervous system (CNS), sources of calcium influx, including those arising from Gq activation can be observed in targeted cells types like neurons or astrocytes. This powerful genetic method allows simultaneous monitoring of the activity of dozens of cells upon activation of endogenous Gq-coupled GPCRs. Therefore, in combination with pharmacological tools, this strategy of monitoring GPCR activation is amenable to high throughput analysis of orthosteric and allosteric ligands of Gq coupled receptors in their endogenous environments.